KERTAPATI WOODLAND: AN ENERGY REVOLUTION TO PALEMBANG ECO-CITY - Chairul Murod (Journal of Architecture&ENVIRONMENT, 2012)
In last three decades, big cities in Indonesia are more getting enlarged. This seems as an improvement. But what missed is the bigger the city, the larger capacity to hold and the more problems to resolve. Meanwhile, Europe and America have decided to keep their cities as small as it is. They divided it into smaller clusters, which are limited, settled, comprehensive, and eco-friendly. This concept known as ‘ecological city,’ replaced ‘classic city’ which has failed to prove an ideal condition and in contrary, add bunch of problems. Palembang city, which already large planned to go International in 2013: a wealthy, cultural, and religious city becomes our concern. The current Major commits to limit this city which is matched to ecological city theory. This is showed in 2014 city landscape plan. As a starter, one area needs to be managed is Kertapati. This area has a potency to develop, but not yet seen by investor or other economists. This paper talks about this issue, entitled “Kertapati Woodland: An Energy Revolution to Palembang Eco-City”. Talks about creating Kertapati Area to be innovative and smart one; settled, comprehensive, and synergized to its environment targeted complete in 2033. This will be done by society’s involvement and comprehensive planning to: settlement, energy efficiency, water use & management, transportation system, and area management.